Studies in the archaeology of the medieval Mediterranean
1 online resource.
Keywords: The medieval Mediterranean world has inspired a rich variety of archaeological studies aimed at trying to piece together its past. This volume presents seven case studies that reveal the complexities of and possible solutions for exploring various areas of the Mediterranean basin. Individually, they offer models of interdisciplinary study that move beyond the disciplinary boundaries of archaeology to integrate evidence from other fields ranging from history to town planning. As a whole, they provide the only collection of studies of their kind for the medieval Mediterraean. They thus provide readers with a view of a field that is vibrant, nuanced, and utilizes a methodological approach that is capable of greatly increasing our knowledge of the medieval Mediterranean world. Contributors are Tasha Vorderstrasse, Jon van Leuven, Cédric Devais, Michelle Hobart, Giulia Annalinda Neglia, Johnny De Meulemeester, and Sauro Gelichi.